2014
DOI: 10.1007/978-3-319-08404-6_8
|View full text |Cite
|
Sign up to set email alerts
|

Reconfiguring Independent Sets in Claw-Free Graphs

Abstract: Abstract. We present a polynomial-time algorithm that, given two independent sets in a claw-free graph G, decides whether one can be transformed into the other by a sequence of elementary steps. Each elementary step is to remove a vertex v from the current independent set S and to add a new vertex w (not in S) such that the result is again an independent set. We also consider the more restricted model where v and w have to be adjacent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 34 publications
1
71
0
Order By: Relevance
“…• Token Sliding (TS rule) [6,7,10,11,19,23]: This rule corresponds to sliding token, that is, we can slide a single token only along an edge of a graph.…”
Section: Related and Known Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…• Token Sliding (TS rule) [6,7,10,11,19,23]: This rule corresponds to sliding token, that is, we can slide a single token only along an edge of a graph.…”
Section: Related and Known Resultsmentioning
confidence: 99%
“…• Token Jumping (TJ rule) [7,15,19,23]: A single token can "jump" to any vertex (including non-adjacent one) if it results in an independent set. • Token Addition and Removal (TAR rule) [2,5,13,19,[21][22][23]: We can either add or remove a single token at a time if it results in an independent set of cardinality at least a given threshold minus one.…”
Section: Related and Known Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polynomial-time algorithms have been developed for shortest transformation under TS for proper interval graphs, trivially perfect graphs, and caterpillars [58] (though NP-hard in general for all reconfiguration steps [17]), for connectivity under TS for interval graphs [56] and under TAR for cographs [55], and for finding an actual reconfiguration sequence under TS for trees (as an extension of the reachability algorithm) [59]. It has also been shown that there is an infinite family of instances on paths for which the length of the reconfiguration sequence is at least quadratic in the number of vertices [59]; in contrast, for every yes-instance of reachability on cographs, there is a bound on the length of the reconfiguration sequence [42] as well as a bound on the diameter for claw-free graphs [57]. In other work, the idea of reconfiguration of independent sets in graphs has been extended to reconfiguration of independent sets in matroids [64].…”
Section: Analysis Using Graph Classes For Independent Setmentioning
confidence: 99%
“…Reconfiguration graphs have been studied for a number of combinatorial problems; the questions asked are typically (as we have seen for colouring) is the graph connected?, what is the diameter of the graph (or of its connected components)?, how difficult is it to decide whether there is a path between a pair of given solutions? Problems studied include boolean satisfiability [13,21],clique and vertex cover [16], independent set [6,20], list edge colouring [17],shortest path [3,4], and subset sum [15] (see also a recent survey [14]). Recent work has included looking at finding the shortest path in the reconfiguration graph between given solutions [19], and studying the fixed-parameter-tractability of these problems [7,18,23,24].…”
Section: (The Answer Is Always Yes)mentioning
confidence: 99%